Augmented Reality-Mediated Inquiry Learning: Investigating Impacts on Student Achievement and Engagement in Geography - Syamsunardi; Arfandi Arfandi; Hasnita Riska; Paige Sarlin (CV Bumi Spasial, 2025)
This study evaluates the effectiveness of the inquiry learning model supported by augmented reality (AR) media in enhancing geography learning outcomes among tenth-grade students at UPT SMAN 11 Sinjai. The research employs a Classroom Action Research (CAR) design conducted over two cycles, involving 28 students. Data were collected through tests and observations and analyzed using a descriptive approach. The results indicate a significant improvement in student learning outcomes, with the average score increasing from 59 in Cycle I to 76 in Cycle II. This improvement suggests that the combination of inquiry learning and AR media effectively enhances students' understanding of complex geographical concepts, particularly volcanism and its impact on life. The study underscores the potential of AR-supported inquiry learning in fostering greater student engagement and critical thinking skills. Future research could further explore the broader application of this approach across different subjects and educational contexts.